Chương II : Số nguyên

Linda Linda

Tìm x

(x – 2) . (y + 1) = 23

( – 9) . ( – 36) = 0

– 15x – 18x + 13x = – 4600

Nguyễn Lê Phước Thịnh
Nguyễn Lê Phước Thịnh CTV 2 tháng 5 2020 lúc 13:02

a) Ta có: (x-2)(y+1)=23

⇔x-2;y+1∈Ư(23)

\(\Leftrightarrow\left[{}\begin{matrix}\left\{{}\begin{matrix}x-2=1\\y+1=23\end{matrix}\right.\\\left\{{}\begin{matrix}x-2=-1\\y+1=-23\end{matrix}\right.\\\left\{{}\begin{matrix}x-2=23\\y+1=1\end{matrix}\right.\\\left\{{}\begin{matrix}x-2=-23\\y+1=-1\end{matrix}\right.\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}\left\{{}\begin{matrix}x=3\\y=22\end{matrix}\right.\\\left\{{}\begin{matrix}x=1\\y=-24\end{matrix}\right.\\\left\{{}\begin{matrix}x=25\\y=0\end{matrix}\right.\\\left\{{}\begin{matrix}x=-21\\y=-2\end{matrix}\right.\end{matrix}\right.\)

Vậy: (x,y)∈{(3;22);(1;-24);(25;0);(-21;-2)}

c) Ta có: \(-15x-18x+13x=-4600\)

\(\Leftrightarrow-20x=-4600\)

hay x=230

Vậy: x=230

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN